Association of bioavailable inhibin B and oocyte yield in controlled ovarian stimulation - Rachel B. Danis, M.D., M.S; Intira Sriprasert, Ph.D; Jacqueline R. Ho, M.D., M.S; Lynda K. McGinnis, Ph.D; Ajay Kumar, Ph.D; Frank Z. Stanczyk, Ph.D (Elsevier, 2021)
Objective: To determine if the biologically active or bioavailable inhibin B (bio-inhB) correlated with the oocyte yield in controlled ovarian stimulation (COS). Design: Cross-sectional study. Setting: Academic center. Patient(s): Women undergoing oocyte cryopreservation. Intervention(s): None. Main Outcome Measure(s): Serum of women were sampled to measure bio-inhB at three points: baseline ("start"); middle ("mid"); and end of COS. A validated, highly specific enzyme-linked immunosorbent assay (Ansh Labs, Webster, TX) measured bio-inhB. The Spearman tests analyzed correlations between bio-inhB and other ovarian reserve markers, including age, follicle-stimulating hormone (FSH), antral follicle count (AFC), and antimüllerian hormone (AMH), and correlations between these markers and oocyte yield. Result(s): A total of 144 women were included. Bioavailable inhibin B at the mid and end of COS, plus its delta, were strongly correlated with other ovarian reserve markers. As the bio-inhB concentration increased, the AFC and AMH levels also increased, whereas the FSH concentration and age decreased. Bioavailable inhibin B values, except at the start of COS, were more strongly correlated with oocyte yield than the FSH concentration (r = 0.72-0.82 vs. r = −0.44) and correlated similarly to the AFC and AMH concentration (r = 0.79 and 0.81, respectively). These correlations strengthened in those with diminished ovarian reserve, specifically age ≥35 years or AMH concentration <2 ng/mL (r = 0.71-0.86 vs. r = 0.49-0.67). Conclusion(s): Predicting COS outcome is imperfect. When using a highly specific enzyme-linked immunosorbent assay, bio-inhB correlated with the oocyte yield similar to or more strongly than traditionally used ovarian reserve markers. These correlations strengthened in cases of diminished ovarian reserve. Bioavailable inhibin B provides physicians with an additional clinical tool for estimating COS outcome.